ANALISIS PENGARUH TARIF PAJAK, SANKSI PAJAK DAN KEADILAN PAJAK TERHADAP TINDAKAN PENGGELAPAN PAJAK (TAX EVASION) - Alika Juliana Putri; Siti Asmonah (JEKOS (Jurnal Ekonomi Dan Sosial), 2025)
This study aims to analyze the influence of tax rates, tax sanctions, and tax fairness on tax evasion behavior among individual taxpayers at the Pratama Tax Office (KPP Pratama) Cibinong, Bogor. The background of this research is based on the phenomenon of low taxpayer compliance and the occurrence of tax evasion cases, despite the implementation of a self-assessment system in Indonesia. This research employs a quantitative approach using a survey method with questionnaires. The sample consists of 100 individual taxpayers. The data were analyzed using multiple linear regression analysis. The results show that the tax rate does not have a significant partial effect on tax evasion behavior, while tax sanctions and tax fairness have a significant partial effect. Simultaneously, tax rates, tax sanctions, and tax fairness have a significant effect on tax evasion behavior. These findings indicate that although the tax rate is not always the primary factor, the enforcement of tax sanctions and the perception of fairness in the tax system play an important role in reducing tax evasion behavior.   Keywords: Tax Rate, Tax Sanctions, Tax Fairness, Tax Evasion, Individual Taxpayer.